Advances in smart delivery of food bioactive compounds using stimuli‐responsive carriers: Responsive mechanism, contemporary challenges, and prospects. Issue 6 (19th October 2021) - Shishir, Mohammad Rezaul Islam; Gowd, Vemana; Suo, Hao; Wang, Mingfu; Wang, Qiang; Chen, Feng; Cheng, Ka‐Wing
Abstract: Many important food bioactive compounds are plant secondary metabolites that have traditional applications for health promotion and disease prevention. However, the chemical instability and poor bioavailability of these compounds represent major challenges to researchers. In the last decade, therefore, major impetus has been given for the research and development of advanced carrier systems for the delivery of natural bioactive molecules. Among them, stimuli‐responsive carriers hold great promise for simultaneously improving stability, bioavailability, and more importantly delivery and on‐demand release of intact bioactive phytochemicals to target sites in response to certain stimuli or combination of them (e.g., pH, temperature, oxidant, enzyme, and irradiation) that would eventually enhance therapeutic outcomes and reduce side effects. Hybrid formulations (e.g., inorganic–organic complexes) and multi‐stimuli‐responsive formulations have demonstrated great potential for future studies. Therefore, this review systematically compiles and assesses the recent advances on the smart delivery of food bioactive compounds, particularly quercetin, curcumin, and resveratrol through stimuli‐responsive carriers, and critically reviews their functionality, underlying triggered‐release mechanism, and therapeutic potential. Finally, major limitations, contemporary challenges, and possible solutions/future research directions are highlighted. Much more research is needed to optimize the processing parameters of existing formulations and to develop novel ones for lead food bioactive compounds to facilitate their food and nutraceutical applications.